Impact of hot molding temperature and duration on braking behavior of friction material. (September 2020) - Hentati, Nesrine; Kchaou, Mohamed; Cristol, Anne-Lise; Elleuch, Riadh; Desplanques, Yannick
The manufacturing process of brake materials used for braking applications consists of a succession of steps among which the hot molding has a major impact on properties and performance of materials. In this paper, impact of hot molding temperature and duration on mechanical and thermal properties of friction materials developed with simplified formulation was investigated. Two different hot molding conditions were studied: condition 1 (low temperature associated to long duration) and condition 2 (high temperature associated to short duration). Braking behavior, thermo-mechanical phenomena and wear and friction mechanisms were also investigated. Results indicated that hot molding conditions did not significantly affect mechanical properties and tribological behavior, but they had impact on thermal properties (material molded according to condition 1, material A presented a higher thermal conductivity) and on wear mechanisms involved in the contact. In addition, results revealed that the studied hot molding conditions impacted thermal localization recorded during braking that was denser for the disc rubbed against material B (material molded according to condition 2).